Insight into the antifungal mechanism of Neosartorya fischeri antifungal protein. Issue 7 (22nd May 2015) - Virágh, Máté; Marton, Annamária; Vizler, Csaba; Tóth, Liliána; Vágvölgyi, Csaba; Marx, Florentine; Galgóczy, László
Abstract: Small, cysteine-rich, highly stable antifungal proteins secreted by filamentous Ascomycetes have great potential for the development of novel antifungal strategies. However, their practical application is still limited due to their not fully clarified mode of action. The aim of this work was to provide a deep insight into the antifungal mechanism of Neosartorya fischeri antifungal protein (NFAP), a novel representative of this protein group. Within a short exposure time to NFAP, reduced cellular metabolism, apoptosis induction, changes in the actin distribution and chitin deposition at the hyphal tip were observed in NFAP-sensitive Aspergillus nidulans. NFAP did show neither a direct membrane disrupting-effect nor uptake by endocytosis. Investigation of A. nidulans signalling mutants revealed that NFAP activates the cAMP/protein kinase A pathway via G-protein signalling which leads to apoptosis and inhibition of polar growth. In contrast, NFAP does not have any influence on the cell wall integrity pathway, but an unknown cell wall integrity pathway-independent mitogen activated protein kinase A-activated target is assumed to be involved in the cell death induction. Taken together, it was concluded that NFAP shows similarities, but also differences in its mode of antifungal action compared to two most investigated NFAP-related proteins from Aspergillus giganteus and Penicillium chrysogenum .